Socialization of the use of medicinal plants to improve family health resilience in Keliling Benteng Ulu Village, Banjar Regency - Fahrina Ulfah; Lena Rosida; Ahmad Husairi; Oski Illiandri; Nika Sterina Skripsiana; Rizqi Rifani (Universitas Muhammadiyah Magelang, 2023)
Indonesia is rich in biodiversity, including medicinal plants. Family medicinal plants are cultivated for the prevention and treatment of diseases. Plants in wetlands have played a vital role in the daily life of local communities, but traditional knowledge has declined with the degradation and change of wetlands. To overcome this, community service activities were carried out in the Village of Keliling Benteng Ulu, Banjar Regency in the form of lecture and distribution of medicinal plant seeds. This activity is aimed to increase the knowledge of villagers about the use of family medicinal plants. The result of this activity is an increase in knowledge related to the use of family medicinal plants for family health resilience.